Seasonal biophysical interactions in tidal marsh evolution: insights from a synchronized dataset in Jiangsu, China - Chen, Lei; Moeller, Iris; Zhou, Zeng; Hu, Zhan; Zhang, Yanan; Chu, Mengwei; Jia, Yifei; Townend, Ian; Zhang, Changkuan (Frontiers in Marine Science, 2024)
Introduction Tidal marsh wetlands provide essential and valuable services to the wider interconnected marine and coastal environment, although the complex intertwined processes in morphological evolution remain insufficiently understood owing to synchronized data scarcity, limiting the development of numerical models and management strategies. Methods This study investigated the hydrodynamic, biological, sediment and morphological processes on the Doulong tidal wetlands, Jiangsu, China, using a one-year field dataset that captured spatial and seasonal variations. Results and discussion Our results indicate that biophysical interactions among multiple processes could result in some overlooked sedimentary behaviours and bio-morphological patterns in tidal marsh wetlands. Firstly, the dominance of alongshore currents caused a rapid alongshore expansion of saltmarsh patches, by which the marsh edge achieved seaward advancing, markedly different from the widely reported cross-shore expansion. Secondly, results showed that the particle size of sediment near the marsh edge coarsened when plants withered and then fined when plants grew, indicating that the seasonal variation trend of sediment grain size in saltmarshes was opposite to the trend of vegetation biomass. Thirdly, the interaction between vegetation and stranded marine debris formed banded debris zones within the saltmarsh, where debris bands could cause a biomass reduction of up to 58%, disrupting the commonly-observed parabolic biomass-elevation relationship. Meanwhile, the seasonal variation of vegetation and hydrodynamics could alter the debris positions and hence result in the formation of multiple parallel debris bands. Overall, this study provides a synchronized dataset and elucidates specific bio-morphological relationships and processes that have thus far not been systematically documented, enhancing the comprehensive understanding of tidal marsh wetland evolution.